The Use of Grammarly Software in Mastering Paragraph Writing: A Systematic Literature Review - Moh Moqsith (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Writing is an essential skill in language learning development, and it is compulsory to be mastered by the EFL students in writing paragraph and improve their writing skills. However, there are a lot of students who have difficulty in writing paragraph such as grammatical error, spelling error, and ect. To overcome these problems, students need some tool to correct their error writing automatically for example Grammarly software. The findings of this study showed there are several benefits that will be able to help us in correcting the mistakes that we often experience when we write, being able to identify errors which include organization, diction, language use (grammar), mechanic (spelling and punctuation). This study uses a systematic literature review. Next, it explore how does Grammarly software work to increase students’ capacity in writing paragraph. Therefore, it software is helpful for the students to overcome the problem in their writing paragraph and a combination between traditional feedback and Grammarly feedback is the best method for writing paragraph. Even though Grammarly software has been proven to have a very large impact on student development in terms of writing, it seems that the software still has shortcomings such as in providing feedback with language structures that are still poorly understood. The conclusion show that a combination between Grammarly feedback and manual feedback is needed to make our writing satisfactory and it spite of our error writing. Keywords: Grammarly Software, Paragraph Writing, Systematic Literature Review